Odd Couples : Friendships at the Intersection of Gender and Sexual Orientation - Muraco, Anna, 1969- (Book collections on Project MUSE., 2012)
Muraco studies friendships between straight women and gay men and straight men and lesbians to consider how their relationships both challenge and reinforce conventional notions of sexuality and gender. Based on in-depth interviews, the book considers how people experience gender and sex roles differently within these intersectional relationships.